Evaluation of types of poisoning exposure calls managed by the Malaysia National Poison Centre (2006–2015): A retrospective review. Issue 12 (31st December 2018) - Tangiisuran, Balamurugan; Jiva, Maryam; Ariff, Adilah Mohamed; Abdul Rani, Noor Afiza; Misnan, Asdariah; Rashid, Sazaroni Md; Majid, Mohamed Isa Abdul; Dawson, Andrew H
Abstract : Objective: Accidental or intentional poisoning is a public health concern requiring intervention. The current study designs to evaluate the types of poisoning exposure calls received by the Malaysia National Poison Centre (NPC) over a 10-year period. Settings and data sources: The poisoning enquiries database (2006–2015) from the Malaysia NPC was used for the analysis. Participants: The NPC records all telephone calls that it manages using a validated and standardised form. Demographics and types of the poisoning exposure calls were extracted and descriptive analysis was applied. Primary and secondary outcomes: The primary outcome of this study is to evaluate NPC data for trends in the poisoning exposure calls based on the types and modes of poisoning over a 10-year period. The secondary outcome is to evaluate the characteristics of human exposure cases based on the calls received by the NPC. Results: There was a notable increase in the number of poisoning exposure calls noticed during the 10-year period but dropped significantly in 2012. The highest number of poisoning exposure calls came from Selangor (21.0%), Perak (18.0%) and Negeri Sembilan (9.8%). More than half of the exposure was intentional (53.8%) involving more women (50.3%) as compared with men (41.9%), and in the 20–29 years age group category (33.5%). Exposure mostly occurred at home (96%) through the ingestion route (94.1%). Pharmaceutical products (40.5%), pesticides (31.7%) and household products (20.1%) were the common agents implicated for intentional exposure. Conclusions: There is an increasing trend in enquiries on poisoning exposure calls made to the NPC. Most of the intentional poisoning exposures occurred among younger women and involved pharmaceuticals, pesticides or household products. Poisoning safety education and other interventions are needed to curb poisoning incidents.